ANGIOSARCOMA PILORUS: LAPORAN KASUS - Ammar, Faiq Muhammad; Khalik, Arief Ismail (Medical and Health Journal, 2024)
Angiosarcoma is a type of soft tissue cancer originating from blood vessel endothelial cells that is rare and very aggressive. Angiosarcoma has a poor prognosis with low survival rates. There is no standard management that can be used as a guide for treatment, making it a challenge for the treating team. This case report aims to examine further the clinical manifestations, diagnosis and treatment of pyloric angiosarcoma. We report a case of a 55 year old woman with complaints of black stools, accompanied by hard and difficult bowel movements, upper left abdominal pain and heartburn that felt all the way to the back, a bloated stomach, weight loss, and appetite. Esophagogastroduodenoscopy examination showed a mass in the gastric antrum. Abdominal CT scan with contrast shows a mass with centripetal filling enhancement that is attached and difficult to separate from the pyloric structures of the stomach. Laparotomy, excision of the tumor mass and pyloric resection, duodenal gastric anastomosis were performed in this patient. Anatomical pathology examination gave results of angiosarcoma.